Association of microfilament bundles with lysosomes in polymorphonuclear leukocytes (The Rockefeller University Press, 1976)
The juxtaposition of microfilament bundles and lysosomes seen both in thin-sectioned cells in the transmission electron microscope and in cryofractured cells in the scanning electron microscope, and the presence of short filamentous structures between lysosomes and microfilament bundles, suggest that microfilaments may be attached to lysosomal membranes and that these filaments may be involved in lysosomal movements. Further work is in progress to test these hypotheses.